Optimal adjuvant radiotherapy dose for stage I, II or III Merkel cell carcinoma: an analysis of the National Cancer Database. (7th November 2019) - Yusuf, Mehran; Gaskins, Jeremy; Wall, Weston; Tennant, Paul; Bumpous, Jeffrey; Dunlap, Neal
Abstract: Background: We performed an analysis of the National Cancer Database to determine optimal doses of conventionally-fractionated adjuvant radiotherapy for patients with stage I/II or III Merkel cell carcinoma. Methods: The cohort included 2735 patients with resected Merkel cell carcinoma of the head and neck, trunk or extremities receiving radiotherapy. Exclusion criteria included doses of radiotherapy <30 or >80 Gy, or dose per fraction >200 or <180 cGy. Recursive partitioning analysis and spline models were used to select dose thresholds. Multivariable Cox regression was performed to validate thresholds with respect to overall survival. Results: Recursive partitioning analysis models defined a threshold of 57 Gy for stage I/II Merkel cell carcinoma, above which 3-year overall survival rate was decreased ( P < 0.0001). The 3-year overall survival rate for patients receiving 50.0–57.0 Gy (81.2%) was greater compared to doses of 30.0–49.9 Gy (75.3%) or >57.0 Gy (70%, P < 0.0001). Doses > 57.0 Gy were associated with an increased hazard of death (1.31, confidence interval 1.07–1.60) with respect to doses of 50.0–57.0 Gy. Doses < 50.0 Gy for stage III Merkel cell carcinoma were associated with worsened 3-year overall survival ( P < 0.0001) and increased hazard of death (2.01, confidence interval 1.43–2.82) with respect to doses between 50.0 and 57.0 Gy. Conclusions: Our results support doses of 50–57 Gy for most patients with stage I/II Merkel cell carcinoma receiving conventionally-fractionated adjuvant radiotherapy. In contrast to a prior National Cancer Database analysis, our results suggest doses ≥ 50 Gy should be strongly considered for patients with stage III Merkel cell carcinoma regardless of anatomic subsite. Abstract : Adjuvant radiotherapy doses of 50–57 Gy were optimal for patients with stage I/II Merkel cell carcinoma. Doses ≥ 50 Gy should be strongly considered for stage III patients.